EFFECTS OF QUENCHING-MEDIUM ON THE CRYSTAL STUCTURE OF ASSAB-CORAX STEEL - Aziz K. Jahja; Nurdin Effendi (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2004)
EFFECTS OF QUENCHING-MEDIUM ON THE CRYSTAL STUCTURE OF ASSAB-CORAX STEEL. X-ray diffraction experiment was carried out on commercial Assab-Corax steel sample. The samples were quenched after heat-treated at 920 °C in three different media, air, water and brine. The main objective wasto check on any significant changes occurring in the crystal-structure of the sample, before tempering could becarried out. The x-ray diffraction intensity was collected using the step counting method with a 0.05°stepscan and 2 second preset time. The refinement was carried out using the lm3m model, and results show that the Carbon atoms are distributed among the base position in the body centered cubic unit cell at the eight-fold octahedral interstitial sites. It was verified that although there is a slight expansion in the lattice parameter due to lattice distortion effected by the carbon atoms and a variation in terms of relative peak intensities and theFWHM values, no fundamental structural changes have taken place after the 920 °C pie-tempering heat-treatment. It was found that alloys quenched in a brine medium, have the best chance to conserve both the crystalline structure and the hardness property of the original untreated sample. The highest hardness value is from the brine-quenched medium at (373±4) HVN which lies within the experimental error of the untreatedsample’s hardness (382±21) HVN. In the air- and brine quenched samples, the highest inhomogenous strain-field is in the [/10] crystal direction, and is lowest in the [220] direction. Whereas for the water-quenchedsample, these directions are the [3/0] and the [/10] respectively.